Bakers’ street product (Chicken pie) / Siti Aminah Salleh - Salleh, Siti Aminah (2009)
This case study will be focus on many Ayamas products why Bakers’ Street Chicken pies brand is not accept by the customer and this product is the lowest sales compared with other Ayamas products. For this study, researcher used primary and secondary data. For primary, researcher used some interview with the person in charge for this product and other main power for distribute this product. For secondary data, researcher get from annual report, sales summary, Ayamas slide from the presentation, references book, journal and etc. The scope of this case study is how Ayamas can maintain the market leader for further process chicken product in the market although the Bakers’Street Chicken pies cannot accept from customer and the procedures that they used to be maintain as a market leader. Besides that the scope of the study that researcher wants to know is the short term strategic planning that Ayamas can do to increasing the sales of Bakers’ Street product for short term period and the lastly is the long-term strategic planning for Bakers’ Street Chicken pies for future time. For the findings, researcher got the procedures that Ayamas used to maintain their market leader. Among the procedures that Ayamas used is SWOT and TOWS Analysis, IFE and EFE Matrix. And this is evident with the marketing theory. Other than that the short-term strategic planning for their Bakers’ Street Chicken pies is, Ayamas want to improve their distribution channels, do the attractive product sampling and do the branding activities. For the long term strategic planning that Ayamas want to do improve and increase High traffic Outlet and Shop In Shop strategy. The conclusion for this case study, although Ayamas is a market leader in further process chicken product in the market and it is evident from the marketing theory but Ayamas used a wrong strategy planning for their Bakers’ Street Chicken pies product.